Identification and validation of a prognostic model of necroptosis-related lncRNAs in hepatocellular carcinoma - Chen, Min; Wu, Guang-Bo; Hua, Shan; Zhao, Zhi-Feng; Li, Hong-Jie; Luo, Meng (Frontiers in Genetics, 2022)
Abstract: Background: The study focused on establishing a prognostic survival model with six necroptosis-related lncRNAs to predict overall survival (OS) in patients of hepatocellular carcinoma (HCC). Methods: The data of gene expression and clinical information of HCC patients was obtained from The Cancer Genome Atlas (TCGA). Cox regression with LASSO was used for constructing a necroptosis-related lncRNA survival model, which we further validated it with qRT-PCR in vitro. The relatively bioinformatics analysis and consensus cluster analysis were performed based on six differentially expressed lncRNAs. Results: The survival prognostic model was constructed with using data from TCGA. Receiver operating characteristic (ROC) curves showed a good survival prediction by this model. GSEA showed that several signaling pathways were related to HCC progression. Immuned-related functional analysis showed that aDCs, macrophages, Th2 cell and Treg have stronger correlation with the high-risk group. The consensus cluster analysis further validated the 6-lncRNA prognostic model. Conclusion: A novel 6-lncRNA (AL606489.1, NRAV, LINC02870, DUXAP8, `ZFPM2-AS1` and AL031985.3) prognostic model had an accurately predictive power in HCC prognosis, which might be worthy of clinical application. Keywords: hepatocellular carcinoma; prognostic model; necroptosis; lncRNA